Judean personal names in the book of Jeremiah in light of archaeological evidence - Golub, Mitka R; Golani, Shira J. (2018)
The relationship between the book of Jeremiah and the archaeological data can be viewed through the lens of Judean personal names from the 7th to the early 6th centuries BCE. Previous onomastic studies have searched the epigraphic record for names of individuals mentioned in Jeremiah. This study, however, analyzes and compares characteristics of personal names in both sources, such as name type, the existence and type of theophoric elements, the location of the theophoric element in a name (either prefixed or suffixed), the יהו-יהand יהו-יוvariants, and popular names. The comparison reveals similarities between Judean personal names in Jeremiah and those found in the archaeological data, indicating that the book of Jeremiah probably reflects authentic pre-Exilic Judean onomastic traditions. Nevertheless, the differences found in the distribution of יהוand יהbetween names in Jeremiah and the archaeological data may demonstrate that the names in Jeremiah were affected by redaction.
Keywords: Archaeology and the Bible; First Temple period; Iron Age II; Jeremiah; Judah; Judean onomastics; Yahwistic names; Personal Names; Redaction